Influence of functionalized nanosilica with different functional groups in the properties of cementitious composites: A review (Research, Society and Development, 2021)
The use of supplementary nano cementitious material (SNCM) to improve the mechanical properties and durability performances of cementitious composites (cement paste, mortar and concrete) has received remarkable attention in recent studies. The use of nanosilica as SNCM is a consolidated practice in the scientific community. However, recent developments in the synthesis of monodisperse and narrow-size distribution of nanoparticles by functionalization methods provide a significant improvement to the development of silica-group nano composites (among the functional groups: amine, carboxyls and glycol groups), the so-called functionalized nanosilica (FNS). This article aims to raise a literature review on the properties of FNS in cementitious materials and the advanced techniques of nano/micro structural analysis used to characterize cementitious composites containing FNS’s.